Sociological Analysis of the Relationship between Socio-Economic Indicators and Death Rate in Iran During 1991-2019 - Siroos Ahmadi; Arman Heydari; Zahra Shakeri (توسعه اجتماعی)
The death rate in Iran has experienced different fluctuations in recent decades. Although, this issue has been widely studied due to its importance, it has rarely been paid attention from a macro and long-term perspective. Therefore, this research has tried to investigate the relationship between socio-economic indicators including; GDP per capita, women's participation in the labor force, inflation and unemployment and literacy rate with the death rate in the period of 1991-2019. This research is a longitudinal quantitative type that was conducted using the time-series method. In order to investigate the short-term and long-term relationship of the research variables, the autoregressive model was used in microfit software. Based on the findings of the research, with the improvement of the literacy (t-ratio:-4.3, pro:.000), the death rate has decreased. In addition, there is a positive and significant relationship between women’s participation in the labor force (t-ratio:8.7, pro:.000) and unemployment (t-ratio:2.5, pro:.023) with death rate, and finally, there is no significant relationship between GDP per capita (t-ratio:1.7, pro:.102) and inflation (t-ratio:-1.7, pro:.098) with death rate. Based on the findings of the research, it is concluded that the death rate in Iran is affected by some macro socio-economic indicators.